DETERMINANTS OF FINANCIAL PERFORMANCE ON THE GO PUBLIC COMPANY ON BEI - Atang Hermawan; Nagian Toni (TRIKONOMIKA, 2020)
The objective of this research is to get an understanding on the effect of the investment decision, capital structure and dividend policy on financial performance using the Multiple Regression Analysis. It is expected that this model will give more comprehensive analysis on the effect of the investment decision, capital structure and dividend policy on financial performance of public companies, which includes the direct or indirect effect on one variable against the others variables. on public companies in Indonesian Stock Exchange in 2014-2017. The findings reveal that, the investment decision has a more dominant effect on financial performance. The investment decision, capital structure and dividend policy have a positive effect on financial performance. The theoretical finding on this research can be developed to make investment decisions, capital structures and dividend policies of public companies. In other words, the three variables will have some means of effect on financial performance, compare with other factors.